Dampak Fluktuasi Dinamis Makro Ekonomi, IHSG, dan SIBOR Terhadap Jakarta Islamic Index - Ris Yuwono Y. Nugroho (Universitas Trunojoyo Madura, 2011)
Capital markets can be a leading indicator for the economy. Shariah Index has taken place in the process of Islamization of capital markets at once is Islamic capital market development. The purpose of this study to (1) know the description of the dynamics of JII, JCI, Index of Industrial Production, and SIBOR, (2) evaluate the response to shocks Jakarta Islamic Index stock index, the Index of Industrial Production, and SIBOR. Analysis using Vector Autoregression. VAR is built with consideration to minimize the theoretical approach capable of capturing economic phenomena. Description JII and JCI showed a similar pattern, the Index of Industrial Production has an increasing trend, while SIBOR fluctuates and tends to fall. Shocks that occurred in the JII, JCI and the Index of Industrial Production will be responded positively by JII, while the shocks that occurred in SIBOR will respond in the opposite direction.